Faith in Paper - Cleland, Charles E., 1936- (Book collections on Project MUSE., 2011)
Organized around eight of the region's most important treaty lawsuits, the book features detailed descriptions and explanations by each case's lead attorney, some of the best legal minds in their field. These lawsuits include cases on fishery and hunting rights (United States v. Michigan; Lac Courte Oreilles v. Wisconsin [Voigt]; Menominee Indian Tribe of Wisconsin v. Thompson; and Mille Lacs Band of Chippewa Indians v. Minnesota); reservation boundaries (Keweenaw Bay Indian Community v. Michigan; Wisconsin v. Stockbridge Munsee Community and Robert Chicks; and County of Mille Lacs v. Melanie Benjamin et al.); and property tax (Keweenaw Bay Indian Community v. Naftaly). Faith in Paper is both an invaluable contribution to the scholarship of American Indian law and a rich resource for Native people themselves as they strive to retain or regain rights that have eroded over the years. --Book Jacket.